2011
DOI: 10.1165/rcmb.2009-0440oc
|View full text |Cite
|
Sign up to set email alerts
|

Protective Properties of Inhaled IL-22 in a Model of Ventilator-Induced Lung Injury

Abstract: High-pressure ventilation induces barotrauma and pulmonary inflammation, thus leading to ventilator-induced lung injury (VILI). IL-22 has both immunoregulatory and tissue-protective properties. Functional IL-22 receptor expression is restricted to nonleukocytic cells, such as alveolar epithelial cells. When applied via inhalation, IL-22 reaches the pulmonary system directly and in high concentrations, and may protect alveolar epithelial cells against cellular stress and biotrauma associated with VILI. In A549 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 47 publications
2
55
1
Order By: Relevance
“…Moreover, recombinant IL-22 applied in the lung improves bacterial clearance (35). IL-22 has also been shown in a model of ventilator-induced lung injury to have potential therapeutic benefit (37). It has been shown that the lack of IL-22 is associated with reduced epithelial repair (38) and increased fibrosis (36) in experimental influenza infection.…”
Section: Il-22 and Mucosal Immunitymentioning
confidence: 99%
“…Moreover, recombinant IL-22 applied in the lung improves bacterial clearance (35). IL-22 has also been shown in a model of ventilator-induced lung injury to have potential therapeutic benefit (37). It has been shown that the lack of IL-22 is associated with reduced epithelial repair (38) and increased fibrosis (36) in experimental influenza infection.…”
Section: Il-22 and Mucosal Immunitymentioning
confidence: 99%
“…IL-22 is also a key factor controlling mucosal immunity and the dissemination of commensal bacteria from the intestinal tract (22). In the lungs, IL-22 protects against experimental lung fibrosis (23) and ventilator-induced lung injury (24). IL-22 also limits Th2-mediated airway inflammation and tissue damage during asthma (25)(26)(27).…”
mentioning
confidence: 99%
“…Once bound to its heterodimeric receptor, namely IL-22R1/IL-10R2, IL-22 will engage signal transduction dominated by activation of STAT3 (3) with subsequent context-specific amplification of anti-apoptotic, tissue protective, anti-bacterial, immunoregulatory, or proinflammatory genes. B cell lymphoma-2 and B cell lymphoma-xl (12), mucin-1 (13), ␤-defensins (14) and lipocalin (15), suppressor of cytokine signaling-3 (16), as well as CXCL8 (17), CXCL5, matrix metalloproteinase-3 (18), and iNOS (19) shall be quoted herein exemplarily. Immunoregulatory properties of IL-22 are likewise strictly context specific and range from protective functions seen in models of infection/microbe-driven inflammation (15,20), hepatitis (12), and ventilator-induced lung injury (16) to a clear pathogenic function seen in models of autoimmunity, specifically collagen-induced arthritis (21), and experimental psoriasis (22).…”
mentioning
confidence: 99%